Tahap kecerdasan emosi pemimpin dan kepimpinan servant serta pengaruhnya terhadap pengurusan perubahan di sekolah - Izani, Ibrahim (2014)
Effective change management is important to ensure that the organization continues to compete. However, 70 percent of program changes implemented in the organization are doomed to failure and need serious consideration, particularly in emotional intelligence and servant leadership aspects.Therefore, this study aimed to identify the influence of emotional intelligence and servant leadership on the change management in schools. In particular, it was to identify the level of change management, emotional intelligence and servant leadership, as well as to examine the significant differences of demographic factor variables, namely age, gender and administrative experience.This study used quantitative research method. Survey instruments involved Emotional Competency Inventory, Change Facilitator Style Questionnaire and Servant Leadership Scale. A total of 342 secondary school teachers in the northern region have participated in this study. Data were analyzed using ANOVA, t-test, correlation, Multiple Regression Analysis and Hierarchical Moderated Multiple Regression. The results showed there was a significant difference in emotional intelligence and servant leadership by gender but not in change management. The results also showed that no significant difference between emotional intelligence, servant leadership and change management by age and administration experience. Furthermore, it was also found that there was a positive significant relationship between emotional intelligence and servant leadership with change management in schools. Result also revealed that emotional intelligence and servant leadership is contributor for change management in schools. The results also recall that servant leadership is a moderator for the relationship between emotional intelligence and change management. In conclusion, this study provided a theoretical framework that shows the contribution aspects of emotional intelligence and servant leadership on change management in schools.